Does Mefloquine (Lariam®) Therapy Improve the Prognosis of Human JC Polyomavirus-Induced Progressive Multifocal Leukoencephalopathy? - Zlatko Kalvatchev; Iliya Tsekov (Journal of Biomedical & Clinical Research, 2014)
Progressive multifocal leukoencephalopathy (PML) is ademyelinating disease caused by infection with Polyomavirus hominis 2, popularly known as JC virus (JCV). The disease is usually fatal as it develops due to the progressive destruction of oligodendrocytes in multiple brain foci. Several substances that show effect against JCV have been investigated. However, only the antimalarial drug mefloquine has been reported to significantly influence the viral replication both in vitro and following in vivo therapy with good penetration and distribution of the drug at efficacious concentrations into the central nervous system (CNS). The current material presents some of the available published data, suggesting that the activity of mefloquine against JCV be considered for treatment of patients with PML.